STAGES OF DEVELOPMENT OF LOGICAL THINKING IN SCHOOL MATHEMATICS COURSES - Ismatov Normurod Asatulla o’g’li; Bayzaqov Maxmud Baxodir o’g’li (Scholars Digest Publishing, 2023)
This article discusses the importance of mathematical problems with original solutions to teach students to think logically and to expand and enrich their imagination.
Keywords: mathematics, logical literacy, elements of logic, logical problems.